Mass deaths of saiga antelopes - A. V. Mischenko; V. A. Mischenko; A. K. Karaulov; A. V. Potekhin; A. P. Mezhnev (Ветеринария сегодня)
The paper presents analytical review of data concerning the reasons for mass deaths of saiga antelopes in Kazakhstan. It was demonstrated that the data on saiga antelope disease etiology are contradictory: pasteurellosis (bovine haemorrhagic septicemia), anaerobic enterotoxemia, ruminai tympany, tryptophan-induced bovine atypical interstitial pneumonia and unknown virus. It means that when investigating the reasons of mass morbidity and mortality in wild ruminants the data of epidemic survey, remote clinical examination, post mortem lesions and results of laboratory tests of pathological samples from dead and killed animals were taken into account. To study the reasons of mass deaths in wild ruminants it is necessary to involve highly qualified specialists experienced in this pathology research. It was shown that clinical and pathological samples collected from dead and killed wild animals shall be tested according to the procedure of precise testing centres also for the purposes of excluding infections pathology and intoxications of different nature.